Personality diatheses and Hurricane Sandy: effects on post-disaster depression - Kopala-Sibley, D. C. (Psychol Med, 2015)
BACKGROUND: According to diathesis–stress models, personality traits, such as negative emotionality (NE) and positive emotionality (PE), may moderate the effects of stressors on the development of depression. However, relatively little empirical research has directly examined whether NE and PE act as diatheses in the presence of stressful life events, and no research has examined whether they moderate the effect of disaster exposure on depressive symptoms. Hurricane Sandy, the second costliest hurricane in US history, offers a unique opportunity to address these gaps. METHOD: A total of 318 women completed measures of NE and PE 5 years prior to Hurricane Sandy. They were also assessed for lifetime depressive disorders on two occasions, the latter occurring an average of 1 year before the hurricane. Approximately 8 weeks after the disaster (mean = 8.40, s.d. = 1.48 weeks), participants completed a hurricane stress exposure questionnaire and a measure of current depressive symptoms. RESULTS: Adjusting for lifetime history of depressive disorders, higher levels of stress from Hurricane Sandy predicted elevated levels of depressive symptoms, but only in participants with high levels of NE or low levels of PE. CONCLUSIONS: These findings support the role of personality in the development of depression and suggest that personality traits can be useful in identifying those most vulnerable to major stressors, including natural disasters.